2008
DOI: 10.1103/physrevlett.101.145702
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Metallic-Glass Cellular Structures Exhibiting Benchmark Strength

Abstract: By identifying the key characteristic ''structural scales'' that dictate the resistance of a porous metallic glass against buckling and fracture, stochastic highly porous metallic-glass structures are designed capable of yielding plastically and inheriting the high plastic yield strength of the amorphous metal. The strengths attainable by the present foams appear to equal or exceed those by highly engineered metal foams such as Ti-6Al-4V or ferrous-metal foams at comparable levels of porosity, placing the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…A possible way to address this issue is to take the inspiration from the structure of a natural bone and introduce porosity into the BMG substrate, i.e., the foamed BMG. [24][25][26] Porosity will also improve osseointegration and implant stabilization with the adjacent tissue. It has been suggested that porosity throughout the entire implant structure could reduce the stiffness of the material, which further addresses the stress shielding issue.…”
Section: Resultsmentioning
confidence: 97%
“…A possible way to address this issue is to take the inspiration from the structure of a natural bone and introduce porosity into the BMG substrate, i.e., the foamed BMG. [24][25][26] Porosity will also improve osseointegration and implant stabilization with the adjacent tissue. It has been suggested that porosity throughout the entire implant structure could reduce the stiffness of the material, which further addresses the stress shielding issue.…”
Section: Resultsmentioning
confidence: 97%
“…To overcome those disadvantages, lots of research works have been focused on the improving of the mechanical properties of these glasses via many different methods; one of these methods is to introduce inhomogeneity with different length scale in the glassy matrix [4][5][6][7][8][9][10][11][12][13]. In this way, heterogeneities can be achieved by fabricating composites with nano-scale inhomogeneities of crystal/quasicrystal phases [4][5][6], by producing porous metallic glass with micron-scale pores in an amorphous matrix [14,15], or by producing phase separated BMG having two or more different amorphous phases separated by different length scales [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the enduring research efforts, malleable MGs have be successfully synthesized/acquired by means of alloy design [13], sample size reduction [9e11, 14,15], formation of porous structures [16,17] and dispersion of toughening phases in the original amorphous matrix [18e20]. Despite the success of these approaches in delaying or even suppressing catastrophic shear banding, it is still an open question for the dominant deformation mechanism that can lead to such a brittle/plastic behavior in different monolithic MGs.…”
Section: Introductionmentioning
confidence: 99%